Improving diabetes care at primary care level with a multistrategic approach: results of the DIAPREM programme - Prestes, Mariana (2017)
To present results, 1 year postimplementation at primary care level, of an integrated diabetes care programme including systemic changes, education, registry (clinical, metabolic, and therapeutic indicators), and disease management (DIAPREM).